Induction motor fault detection and isolation through unknown input observer - Gaeid, K.S.; Ping, H.W. (Academic Journals, 2010)
Unknown input observers (UIO) can be used in the model-based fault detection and isolation (FDI) schemes to reduce or almost eliminate the effect of unknown disturbances on the multi input multi output (MIMO) plant/system. In this paper, a new FDI of the MIMO system was carried out in as well as the design of many fault isolation banks of UIOs has been done. These banks are used to generate residuals that are insensitive to unknown disturbances or noise. To make sure best detection and isolation of the faults, these banks generate residuals, which are sensitive to only one fault. The fault in the actuator is detected and isolated with a lower false alarm rate effectively.